A study on energy dependence of nano barium sulfate powder using the EPR technique in photon, electron and proton beams. (April 2021) - Aboelezz, E.; De Angelis, C.; Fattibene, P.
Highlights: Energy dependence factors for different radiation beams were determined. Nano-barium sulfate has a strong energy dependence. Nano-BaSO4 is a precise, accurate and sensitive dosimeter for each studied beam. Performance parameters for each beam were estimated. Abstract: The Nano-BaSO4 dosimeter features a linear response to dose and low fading, properties for which it has been proposed as an electron paramagnetic resonance (EPR) dosimeter for ionizing radiation. The literature lacks of studies that explore nano-BaSO4 response vs. radiation quality, a critical issue when using any material in beams other than gammas. This work aims at filling this gap by studying the EPR response of BaSO4 nano-powder irradiated to 137 Cs, 6 MV and 15 MV X-rays, 6 MeV and 16 MeV electrons, and 35 MeV protons. Signal line shape and linearity of dose response were unaffected by any type of radiation. Energy dependence was estimated in terms of dose to water, and normalized to 137 Cs energy, leading to values of about 0.70 for electrons, 0.6 for protons, close to 1 for 6 MV photons and 0.87 for the 15 MV photons.